2018
DOI: 10.1055/a-0654-5850
|View full text |Cite
|
Sign up to set email alerts
|

Delitpyrones: α-Pyrone Derivatives from a Freshwater Delitschia sp.

Abstract: In research focused on the discovery of new chemical diversity from freshwater fungi, a peak library was built and evaluated against a prostate cancer cell line, E006AA-hT, which was derived from an African American, as this population is disproportionately affected by prostate cancer. The chemical study of the bioactive sample accessioned as G858 ( sp.) led to the isolation of eight new -pyrone derivatives (1:  - 7: , and 11: ), as well as the new 3,4-7-ethyl-4,8-dihydroxy-3,6-dimethoxy-3,4-dihydronaphthalen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
0
17
0
1
Order By: Relevance
“…Barr, Mycotaxon 76: 109 (2000) The family Delitschiaceae, typified by Delitschia, occurs on bovine dung (Doveri 2011), or rarely on aged wood or plants (Hyde et al 2013). Recent studies by Rivera-Chávez et al (2018) reported Delitschia species from submerged wood in freshwater habitat and Delitschia bispora from a water-cooling tower (Eaton & Jones 1970). Wijayawardene et al (2018) reported three genera in this family (Delitschia, Ohleriella and Semidelitschia), but sequence data is available only for Delitschia.…”
Section: Caryospora Quercusmentioning
confidence: 99%
See 1 more Smart Citation
“…Barr, Mycotaxon 76: 109 (2000) The family Delitschiaceae, typified by Delitschia, occurs on bovine dung (Doveri 2011), or rarely on aged wood or plants (Hyde et al 2013). Recent studies by Rivera-Chávez et al (2018) reported Delitschia species from submerged wood in freshwater habitat and Delitschia bispora from a water-cooling tower (Eaton & Jones 1970). Wijayawardene et al (2018) reported three genera in this family (Delitschia, Ohleriella and Semidelitschia), but sequence data is available only for Delitschia.…”
Section: Caryospora Quercusmentioning
confidence: 99%
“…Wijayawardene et al (2018) reported three genera in this family (Delitschia, Ohleriella and Semidelitschia), but sequence data is available only for Delitschia. Recently identified Delitschia strains from submerged wood show a diversity of important chemicals (Rivera-Chávez et al 2018) that show activity towards prostate cancer cell lines. Study of the bioactive from sample accessioned as G858 (Delitschia sp.)…”
Section: Caryospora Quercusmentioning
confidence: 99%
“…In addition, natural products with α-pyrone sub-structure have antibacterial ( Zhang et al, 2013 ), anti-influenza A virus ( Hou et al, 2018 ), and anti-HIV ( Appendino et al, 2007 ) activities. Some of them are signal molecules ( Brachmann et al, 2013 ), while some are also cytotoxic agents against tumor cells ( Rivera-Chávez et al, 2019 ; Zhu et al, 2019 ). In particular, dibenzo-α-pyrone ( 3 ) belongs to a significant group of heptaketide coumarin metabolites that have a fused tricyclic core ( Figure 1A ), commonly identified from fungi, bacteria, and plants ( Lai et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The family Delitschiaceae is a basal family (along with Massariaceae) in the order Pleosporales (Zhang et al 2012;Hyde et al 2013), comprising mainly terrestrial and saprobic species occurring on herbivore dung (e.g., Kruys et al 2006;Doveri 2011), aged wood, and plants (Hyde et al 2013) or submerged wood (Hyde and Steinke 1996;Rivera-Chávez et al 2019); one species was identified from decaying fruits of Nypa fruticans (Jayasiri et al 2019). The family is monogeneric, including only the genus Delitschia, with relatively few species (Jayasiri et al 2019).…”
Section: Section Editor: Gerhard Ramboldmentioning
confidence: 99%